27‐Hydroxycholesterol, an Endogenous SERM, and Risk of Fracture in Postmenopausal Women: A Nested Case‐Cohort Study in the Women's Health Initiative. (7th December 2018) - Chang, Po‐Yin; Feldman, David; Stefanick, Marcia L; McDonnell, Donald P; Thompson, Bonne M; McDonald, Jeffrey G; Lee, Jennifer S
ABSTRACT: 27‐Hydroxycholesterol (27HC) is a purported, novel endogenous SERM. In animal models, 27HC has an anti‐estrogen effect in bone, and 17β‐estradiol mitigates this effect. 27HC in relation to fracture risk has not been investigated in humans. Depending on the level of bioavailable 17β‐estradiol (bioE2 ), 27HC may increase fracture risk in postmenopausal women and modify the fracture risk reduction from menopausal hormone therapy (MHT). To test these a priori hypotheses, we conducted a nested case‐cohort study of 868 postmenopausal women within the Women's Health Initiative Hormone Therapy (WHI‐HT) trials. The WHI‐HT tested conjugated equine estrogens versus placebo and separately conjugated equine estrogens plus progestin versus placebo. Fracture cases were 442 women who had an adjudicated incident hip or clinical vertebral fracture during the WHI‐HT follow‐up. The subcohort included 430 women randomly selected at WHI‐HT baseline, four of whom had a subsequent fracture. Of the 868 women, 266 cases and 219 non‐cases were assigned to the placebo arms. Cox models estimated hazard ratios for incident fracture in relation to pre‐randomization circulating levels of 27HC and 27HC/bioE2 molar ratio. Models adjusted for age, race/ethnicity, total cholesterol, bioE2, sex hormone‐binding globulin, 25‐hydroxyvitamin D, diabetes, osteoporosis, prior MHT use, BMI, falls history, and prior fracture. In women assigned to placebo arms, those in the middle and the highest tertiles of 27HC/bioE2 had an up to 1.9‐fold (95% confidence intervals, 1.25 to 2.99) greater risk of fracture than women in the lowest tertile. In women assigned to MHT arms, fracture risk increased with continuous 27HC/bioE2 levels but not with categorical levels. 27HC levels alone were not associated with fracture risk. 27HC and 27HC/bioE2 did not modify the fracture risk reduction from MHT. In postmenopausal women, circulating levels of 27HC relative to bioE2 may identify those at increased risk of fracture. © 2018 American Society for Bone and Mineral Research.